2020
DOI: 10.3390/ijerph17114071
|View full text |Cite
|
Sign up to set email alerts
|

Acute Physical Activity, Executive Function, and Attention Performance in Children with Attention-Deficit Hyperactivity Disorder and Typically Developing Children: An Experimental Study

Abstract: A growing number of studies support the theory that physical activity can effectively foster the cognitive function of children with attention-deficit hyperactivity disorder (ADHD). The present study examines the effect of acute moderate physical activity on the executive functions and attention performance of (1) typically developing children (without psychological, psychiatric or neurological diagnosis and/or associated treatment stated in their medical history); (2) treatment-naïve ADHD children; and (3) me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 80 publications
2
19
0
Order By: Relevance
“…The gradual decrease in the SDQ-H/I score from the low to the high PA class suggests that PA may be considered as a health-related behavioral factor for ADHD symptoms at medium and high levels of PA, although the effect sizes were low to medium (0.13 to 0.21). These findings were consistent with several types of research that showed benefits of PA in children with ADHD [ 47 , 48 , 59 ]. Since the difference between levels of PA was not significant through age groups, it might be concluded that there is a specific range of PA that may serve as a protective element against hyperactivity/inattention symptoms.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The gradual decrease in the SDQ-H/I score from the low to the high PA class suggests that PA may be considered as a health-related behavioral factor for ADHD symptoms at medium and high levels of PA, although the effect sizes were low to medium (0.13 to 0.21). These findings were consistent with several types of research that showed benefits of PA in children with ADHD [ 47 , 48 , 59 ]. Since the difference between levels of PA was not significant through age groups, it might be concluded that there is a specific range of PA that may serve as a protective element against hyperactivity/inattention symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…It seems that the intensity and frequency of PA are two important factors in order to produce a positive effect on mental health. Moreover, other studies have reported that a higher level of PA is associated with better mental health [ 1 , 3 , 8 , 24 , 25 , 46 , 47 , 48 ]. For example, children who were physically active 1–3 or ≥4 times per week had a lower rate of internalizing and externalizing disorders in comparison to those who were never active [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research conducted by Miklós et al [ 41 ] involved 150 children (6 to 12 years old), classified into a non-medicated group (25 children in the exercise group and 25 children in the control group), a medicated group (25 children in the exercise group and 25 children in the control group) and a control group (25 children in the exercise group and 25 children in the control group), completing a physical activity session of 20 min at 60% and 80% of the maximal heart rate. Differences were found between the baseline and the result of the interventions in alertness, distraction, divided attention, and content flexibility ( p > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…While pyschostimulants methylphenidate (MPH) or amphetamines remain the first line of ADHD treatment [8][9][10], there is a growing appreciation for the beneficial role of nonpharmacological therapies. These include the use of physical activities such as exercise and sports [11][12][13]. A recent meta-analysis of 30 studies showed that moderate to intense aerobic exercise can be effective in the management of the cognitive and behavioral symptoms of ADHD [14].…”
Section: Introductionmentioning
confidence: 99%